2017
DOI: 10.18203/issn.2454-5929.ijohns20174311
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic interventions in vertigo management

Abstract: <p>Vertigo is a condition associated with a spectrum of symptoms and ~30% of general population experience vertigo in their life time. In spite of being of high clinical importance, the management of vertigo is quite challenging. Though the literature supports the availability of various therapeutic interventions used in vertigo treatment, their effectiveness depends on accurate diagnosis, appropriate use of intervention, and physician’s awareness of the overlap between vestibular, autonomic, and psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Antihistamines may cause sedation which is detrimental for the recovery process. 20 In addition to that, cinnarizine has disadvantage of delaying vestibular compensation, so vestibular rehabilitation exercises can not be started until we stop giving the medication. So, by using epley's maneuver simultaneously, we can avoid both the disadvantages.…”
Section: Diabetesmentioning
confidence: 99%
“…Antihistamines may cause sedation which is detrimental for the recovery process. 20 In addition to that, cinnarizine has disadvantage of delaying vestibular compensation, so vestibular rehabilitation exercises can not be started until we stop giving the medication. So, by using epley's maneuver simultaneously, we can avoid both the disadvantages.…”
Section: Diabetesmentioning
confidence: 99%
“…The efficacy of the beta-histine is due its action on the receptors of the histamine. 22 It is used in the treatment of the vertigo due to different etiologies. The therapeutic effect of the beta-histine depends on the doses and duration of the drug.…”
Section: Beta-histinementioning
confidence: 99%
“…The prevalence of vertigo throughout the world is ~30%, with associated co-morbidity being 3.2%. 2 A study in Germany found that vertigo prevalence was 22.9 percent and 3.1 percent 3 . According to an epidemiological study performed in France, the prevalence of vertigo was 48.3 per cent for one year 4 .…”
Section: Introductionmentioning
confidence: 98%